Genetic and Pharmacologic Inhibition of the Neutrophil Elastase Inhibits Experimental Atherosclerosis. Issue 4 (8th February 2018) - Wen, Guanmei; An, Weiwei; Chen, Jiangyong; Maguire, Eithne M.; Chen, Qishan; Yang, Feng; Pearce, Stuart W. A.; Kyriakides, Maria; Zhang, Li; Ye, Shu; Nourshargh, Sussan; Xiao, Qingzhong
Abstract : Background: To investigate whether neutrophil elastase (NE) plays a causal role in atherosclerosis, and the molecular mechanisms involved. Methods and Results: NE genetic–deficient mice (Apolipoprotein E −/− /NE −/− mice), bone marrow transplantation, and a specific NE inhibitor (GW311616A) were employed in this study to establish the causal role of NE in atherosclerosis. Aortic expression of NE mRNA and plasma NE activity was significantly increased in high‐fat diet (HFD)–fed wild‐type (WT) (Apolipoprotein E −/− ) mice but, as expected, not in NE‐deficient mice. Selective NE knockout markedly reduced HFD‐induced atherosclerosis and significantly increased indicators of atherosclerotic plaque stability. While plasma lipid profiles were not affected by NE deficiency, decreased levels of circulating proinflammatory cytokines and inflammatory monocytes (Ly6C hi /CD11b + ) were observed in NE‐deficient mice fed with an HFD for 12 weeks as compared with WT. Bone marrow reconstitution of WT mice with NE −/− bone marrow cells significantly reduced HFD‐induced atherosclerosis, while bone marrow reconstitution of NE −/− mice with WT bone marrow cells restored the pathological features of atherosclerotic plaques induced by HFD in NE‐deficient mice. In line with these findings, pharmacological inhibition of NE in WT mice through oral administration of NE inhibitor GW311616A also significantly reduced atherosclerosis. Mechanistically, we demonstrated that NE promotes foam cell formation by increasing ATP‐binding cassette transporter ABCA1 protein degradation and inhibiting macrophage cholesterol efflux. Conclusions: We outlined a pathogenic role for NE in foam cell formation and atherosclerosis development. Consequently, inhibition of NE may represent a potential therapeutic approach to treating cardiovascular disease.